3X(n+1)=2X(n+5)

Simple and best practice solution for 3X(n+1)=2X(n+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3X(n+1)=2X(n+5) equation:



3X(X+1)=2X(X+5)
We move all terms to the left:
3X(X+1)-(2X(X+5))=0
We multiply parentheses
3X^2+3X-(2X(X+5))=0
We calculate terms in parentheses: -(2X(X+5)), so:
2X(X+5)
We multiply parentheses
2X^2+10X
Back to the equation:
-(2X^2+10X)
We get rid of parentheses
3X^2-2X^2+3X-10X=0
We add all the numbers together, and all the variables
X^2-7X=0
a = 1; b = -7; c = 0;
Δ = b2-4ac
Δ = -72-4·1·0
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-7}{2*1}=\frac{0}{2} =0 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+7}{2*1}=\frac{14}{2} =7 $

See similar equations:

| 12g-12g+g+2g-2g=19 | | a^2+4a-8=0 | | b-b+4b+b+b-6=12 | | 4.x=-8 | | K-k+k+5k+2=14 | | 3n-3=4n+- | | 6v-6v+3v-1=5 | | -10=4/5x | | 12c+-15c-(-10c)+-11c+11c=7 | | 1/2x+4=9/5 | | -7b+7b-(-14b)-(-3b)+7=-10 | | y=-12.216+41.54 | | C=30.75-0.25x | | 8-9.7t=-67.9 | | 14s+-12s=-14 | | G-2=-1/4(4g-2) | | 2q+15q-(-7)=-10 | | 13d-9d+d-4=11 | | 3x-6-2x+2=3(2x-4) | | 9u-3u-11u-6u=11 | | 0=n+4-1 | | 8(x-2)-5(x+4)=20+4 | | 6d-d+3d+3d-d=20 | | −14=k+6k= | | 200-25x=15x | | -4y-(-7y)+-7y=20 | | k+8=3k+1;3 | | 10x^2+9x-63=0 | | x/4-9=9;36 | | 7b^+21b-196=0 | | x+1/2x+(x+45)=180 | | -5m-(-18m)+m=16 |

Equations solver categories